Perception of chin asymmetries among ecuadorian orthodontists, specialist dentists, students and patients - Ana Paula Armendáriz Salas; Grace Elizabeth Revelo Motta (Editorial Ciencias Médicas, 2022)
Introduction: Previous studies have shown differences in the perception of dental and facial asymmetries between dental professionals and non-experts. However, the literature on differences in the perception of chin asymmetries is limited. Objective: Compare the aesthetic perception of chin asymmetries among orthodontists, specialist dentists, students and patients of the Faculty of Dentistry of the Central University of Ecuador. Methods: Observational, analytical and cross-sectional study. The universe was made up of 36 orthodontists, 77 specialist dentists, 96 students and 2580 patients from this Faculty. The sample size was 30 participants for each group. The transverse position of the chin was digitally modified from 0° to 6° in the photographs of two Ecuadorian subjects (male-female). The evaluation was carried out by means of an analogous visual scale. Results: The photographs of asymmetries of the chin with 0° of deviation were qualified as very aesthetic and the asymmetries with 6° were unsightly for the four groups. Orthodontists, specialist dentists and students considered as an aesthetic limit the 2nd deviation of the chin for the photography of the female and male subject. The aesthetic limits were 2° of deviation for the female subject and 3° for the male subject. Significant differences were found between the groups of evaluators and the photographs (p < 0.05). Conclusions: Orthodontists perceived facial aesthetics close to the norm of chin asymmetry, which has an important role in the perception of facial aesthetics.